ACCOUNTABILITY OF GOVERNMENT BUREAUCRACY AT THE CEMPA SUB-DISTRICT OFFICE, PINRANG REGENCY - Maldun, Syamsuddin (Journal of Research in Social Science and Humanities, 2022)
This study aims to determine the accountability of the government bureaucracy. The type of research used is descriptive qualitative research, and the data collection techniques used are observation, interviews, and documentation. While this research was conducted, interviews were conducted with 7 informants, namely 4 people in the Cempa District Office and 3 people from the Cempa District Community. The results of this study indicate that government bureaucracy accountability at the Cempa District Office has been running well even though there are several obstacles in its implementation, namely the need for online access and clearer information to the public.